Perbanyakan Cendawan Trichoderma spp. pada Berbagai Media Alternatif - Abdillah, Rihan Ali; Shinta Andayani; Rahayu, Yuni Sri; Pratiwi, Tri Yuda; Ferdian, Algis Septi (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2026)
The increasing demand for food crop productivity, such as rice, and the heavy use of synthetic chemical fungicides to eradicate pests (OPT) drive the need for more environmentally friendly pest management solutions that support sustainable systems. This study aims to determine which natural material is the best alternative mass-production medium for Trichoderma spp. fungi isolated using the baiting method. The method used is descriptive quantitative with a comparative approach. The exploration of Trichoderma spp. fungi was conducted using the baiting method, followed by macroscopic and microscopic identification. The alternative mass-production media selected for Trichoderma spp. fungi included cracked corn, cassava peel waste, and rice bran. The success of mass production was analyzed based on the even distribution of mature spores on the medium surface and their spore density value, which must meet the field application standards for biological control agents. Cassava peel waste and cracked corn can be used as natural alternative media for the mass production of Trichoderma spp., as evidenced by the even distribution of spore color on the medium surface and their spore density value that meets field application standards. Keywords: Trichoderma spp.; Isolation; Mass-production media